The margins of nihilism: image and disappearance - Šerpytytė, Rita (Religija ir kultūra, 2009)
The pretext of this article is Lacoue-Labarthe’s text Preface to the disappearance. This article attempts to find access to the “analysis” of disappearance, i. e. to conceptualize a theme of disappearance and link it with the problem of identity and alterity. The appearance and disappearance – motions, by which any identities are being constituted and destroyed – direct, first of all, to the phenomenological tradition. The appearance and disappearance are being understood in phenomenology as characteristics of phenomenon. Discussing the phenomenological tradition, in particular – Sartre’s view, the article raises the question about the nature of the motion of disappearance (as the motion, which destroys identities and indicates or directs to alterities). This article attempts to discuss the disappearance in the context of so-called negative “categories” of nihilism. Thus, disappearance is not disclosed as the motion, which has a structure of proposition, but as négatités – as motion, which has a structure of the experience. But what is the meaning of the experience of disappearance? Lacoue-Labarthe’s text served as a key according to some strategy to choose an author, talking on disappearance. The article looks at how the disappearance in Sartre, Heidegger, Virilio, Severino, Baudrillard’s philosophy is being thematized. Although their approaches to appearance and disappearance differ, they are united by the fact of talking on the experience of appearance and disappearance of some identities – things, entities, reality. The disappearance itself is being treated there as something to be experienced, and to be possible to describe. But what it is not disappearance of things, of entities, of reality, but disappearance itself?How to speak on the conditions of possibility of the “appearance” of “experience”, which is a marginal experience – the experience of somebody’s own disappearance? For the Lacoue-Labarthe’s text explanation the text of another author – Jean-Luc Nancy, To fall from sleep, is being used. Juxtaposition of these two texts serves as a philosophical approach to describe practices that, phenomenologically speaking, is not experienced. It reveals the meaning of disappearance, expressed in Lacoue-Labarthe: disappearance (Nothingness) coincides with the origins of appearance, with what it is a Whole.
Keywords: nihilism; disappearance; appearance; identity; alterity; experience